Numerical investigations of entropy generation to analyze and improve heat transfer processes in electric machines. (November 2016) - Eger, Toni; Bol, Thomas; Daróczy, László; Janiga, Gábor; Schroth, Rüdiger; Thévenin, Dominique
Graphical abstract: Highlights: A new, canonical configuration is proposed in this work. It combines the main features of external flows as well as of internal flows. Entropy generation is analyzed in this configuration numerically. The irreversibility distribution is found to be a promising indicator. It detects regions with a high potential for improving heat transfer. Abstract: A new, canonical configuration is proposed in this work, combining in a single setup the main features of external flows (flow around a cylinder) as well as of internal flows (flow between two concentric cylinders in rotation). This flexible configuration allows parametric investigations of combined transport processes involving both external ( Re ∞ ) and internal ( Re 0 ) flows, as they are found in many technical devices, for instance in electric machines. The present paper first describes and analyzes entropy generation in this canonical configuration numerically for a constant wall heat flux and fixed cylinder ( Re 0 = 0), in order to check if the entropic concept can be used to assess and improve industrially relevant designs. A thermal optimization of the configuration is performed to compare the changes observed between initial and optimized design. Based on this, it is shown that the Second Law Analysis (SLA) can be used to find regions where heat transfer could be intensified. The irreversibility distribution ϕ comparing entropy generation due to dissipation and due to conduction is found to be a promising indicator to detect regions with a high potential for improving heat transfer in technical devices.